SIFAT MEKANIK BIONANOKOMPOSIT FILLER NANOPARTIKEL BIOMASS KULIT ROTAN METODE INJEKSI MOLDING - siti nikmatin (Jurnal Biofisika, 2013)
Rattan biomass is one of the agricultural waste that can be used as a source of cellulose nanoparticle. To produce cellulose nanoparticle bark rattan that is low density, good mechanical properties, natural resources and renewable resources needed a new method of development nanotechnology using hummer mill methods. The purpose of this study is synthesis and mechanical properties of bionanocomposite reinforce cellulose nanoparticle bark rattan used injection moulding. Cellulose nanoparticle is made with mechanical systems (milling and shakers) in size 75 μm and hummer mill t =30 minute. PSA test results produced a maximum particle size of 25.6 nm (number distribution commulant method) at the t =30 minute. Meanwhile, the hardness and impact strength of bionanocomposite show 79.9 HRR and 67.7 J/m.